Comparison of treatment outcomes between combined chemotherapy-radiation therapy (chemo-RT) and radiation therapy alone (RT) for intracranial germ cell tumors in adolescent and young adult patients (AYA) - Warissara Rongthong; Nan Suntornpong; Kullathorn Thephamongkhol; Teeradon Treechairusame (Discover Oncology)
Abstract Background The incidence of intracranial germ cell tumors (iGCTs) in adolescents and young adults (AYA) is lower than that in pediatric patients. However, the recurrence rate of iGCT in AYA patients (7.6%) is higher than in children (2%). The use of iGCTs in the AYA population lacks randomized trials to standardize treatment. Therefore, this study aimed to determine the patterns of practice and outcomes of iGCT in AYA. Methods This single-center retrospective cohort study iGCT patients aged 15 to 39 who were treated at Siriraj Hospital, Thailand, from 2007 to 2019. The patients' charts were reviewed, and the results were compared between those who received chemotherapy combined with radiotherapy (Chemo-RT) and those who received RT alone. Results The median follow-up time was 7.6 years. Eighty-four patients were included in this study: 60 with germinomas and 24 with nongerminomatous germ cell tumors (NGGCT). In the case of NGGCT, the 10-year event-free survival (EFS) and overall survival (OS) were 100% and 100%, respectively, with RT alone. For Chemo-RT, the 10-year EFS was 54.05%, and the 10-year OS was 68.44% (P = 0.640 for EFS and 0.454 for OS). For germinomas, the 10-year EFS was 76.87% with RT alone, and the 10-year OS was 86.40%. For Chemo-RT, the 10-year EFS was 69.63%, and the 10-year OS was 69.63% (P = 0.335 for EFS and 0.022 for OS). Compared with those in the groups treated with Chemo-RT and RT alone adjusted for age > 18 years, primary site, metastasis, type of surgery, field of radiotherapy, sex, serum beta-HCG, and serum AFP, the hazard ratio (HR) of EFS was 2.49 (0.85–7.29) (P = 0.095) and the OS was 2.55 (P = 0.237). Conclusions To the best of our knowledge, we present findings on the outcomes of iGCT patients in the AYA age group. After adjusting the hazard ratio, we found no significant difference between patients who received chemotherapy and those who underwent radiotherapy alone in terms of event-free survival and overall survival. Standardized long-term term survival follow-up and supportive treatment in AYA group is needed to improve the outcome and minimize toxicity in this group. There is a need for further randomized control trials that specifically address the population of patients with AYA to improve our understanding of their potential treatment approaches.